Probiotics in the Prevention of Mucositis in People Undergoing Curative Radiotherapy for their Head and Neck Cancer: A Mini-Review - Krishna, Abhishek; Marakala, Vijaya; T.D’souza, Rashmi; Shenoy, Vinayaka R.; D’souza, Sandeep; Jakribettu, Ramakrishna Pai; Baliga, Manjeshwar Shrinath (Current Probiotics, 2024)
Radiotherapy for head and neck cancer (HNC) is associated with a dose-limiting side effect known as radiation-induced oral mucositis (RIOM), which severely diminishes the quality of life for patients. The best part is that this adverse effect has identified risk factors, enabling the implementation of preventative medication to delay/mitigate the ill effects, colonization of opportunistic microbes, and infection. Clinically, several effective strategies have been developed to prevent severe RIOM. However, there are limited options for solutions that are both advantageous and practical while also being cost-effective to implement. Results from well-designed and carried-out research have indicated that probiotics have potential benefits in both the management and prevention of RIOM. Research using animal models and clinical studies has affirmatively shown that the utilization of probiotic organisms can successfully modify the intensity of inflammation by modifying the composition, metabolism, and functional characteristics of natural microbiota. Furthermore, the majority (3 of 4) randomized, double-blind, placebo-controlled studies revealed that probiotics were beneficial in decreasing RIOM. This article collates and examines the scientific observations, addresses the underlying mechanisms, and explores the potential benefits of probiotics in mitigating the occurrence and severity of RIOM.
Keywords: head and neck cancer